Tax Non-Compliance in the Informal Sector: A Case of Small-And-Medium-Scaled Enterprises at Suame Magazine in the Kumasi Metropolis - Agyei Yeboah, Naomi Owusuaa (2016)
A Thesis submitted to the Department of Accounting and Finance, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the degree of Master of Business Administration (Accounting Option)